Navigating the Intersection of COVID-19 and (Re)new(ed) Calls for Racial Justice: A Qualitative Examination of the Experiences of Diversity, Equity, and Inclusion Professionals in College Athletics During A Year of "Social Justice Awakening" - Nicholas Swim; Robert Turick; Yannick Kluch; Raquel Wright-Mair (University of Kansas Libraries, 2022)
The purpose of this qualitative study was to examine the experiences of diversity, equity, and inclusion (DEI) professionals in the NCAA athletics governance structure. The specific focus was centered on the multiple crises of summer 2020, including both the COVID-19 pandemic and calls for social injustices and its effects on DEI work and the impacts on DEI professionals within college athletics. In total, 23 semi-structured interviews were completed with the DEI professionals, with five major themes emerging from the results, including: (1) Reorganization of Priorities, (2) Reactive vs. Proactive Work, (3) Challenges of Virtual DEI Engagement, (4) Emotional Fatigue, and (5) Validation of DEI work. The implications for future research and practitioners will be further explored.